Solution based synthesis of Cu2ZnSnS4 nanoparticles and thin films for solar cell application - Li, Zhenggang (2014)
Quaternary chalcogenide compound Cu2ZnSnS4 (CZTS) is a promising absorber material for low-cost thin film solar cells owing to the abundance of its constituents, suitable band-gap and high absorption coefficient. Conventionally, CZTS thin films are mainly fabricated using vacuum techniques including evaporation, sputtering and pulsed laser deposition. An encouraging power conversion efficiency of 8.4% has been achieved using vacuum deposition method. However, the vacuum deposition techniques are often associated with high energy input and thus impose a significant cost on the devices. Hence, there is a driving force towards replacing the vacuum deposition method with cost-effective processing techniques. I this thesis, I present the solution-based synthesis of CZTS nanoparticles and the deposition of CZTS thin films. CZTS nanoparticles were successfully synthesized using hot injection method. It was found that the reaction temperature plays an important role in determining the phase formation. At reaction temperature below 200°C, the binary Cu2-xS and ternary CTS form together with quarternary CZTS phases. At reaction temperature of 220 ºC and above, pure quaternary CZTS phase is favored. A detailed investigation of CZTS nanoparticles synthesized at 240°C shows that the nanoparticles have an average size of 19.8 nm and the average ratio of S, Cu, Zn and Sn was estimated to be 4.19: 1.96: 0.80: 1.05. In addition, the optical band gap of the CZTS nanoparticles was estimated to be 1.55 eV based on UV-vis-NIR absorption measurements. The reaction time greatly affects the nucleation and growth of nanoparticles. CZTS nanoparticles formed immediately after injection of S precursor. From 0 min to 30 min, the average size of the nanoparticles gradually increased and the size distribution became narrower. With longer reaction time, the growth of nanoparticles shows the phenomenon of Ostwald ripening. The size and shape of nanoparticles could be controlled through solvent-ligand optimization. With 1,2-dichlorobenzene (DCB) as the solvent and oleylamine (OLA) as the ligand, sub-micrometer size clusters (0 ml OLA), near-spherical shape (0.5 ml OLA), faceted (1 ml OLA), and nanoplates (2 ml OLA) CZTS nanostructures were synthesized. The sulfur precursor is the key parameter that determines the phase formation of CZTS polytypes. Kesterite CZTS were formed using elemental sulfur as the sulfur source, while wurtzite CZTS were produced using 1-dodecanthiol (DDT). The use of thioacetamide (TAA) resulted in the formation of mixture of kesterite and wurtzite phases. Further investigation revealed that the reaction rate of sulfur precursors plays a critical role. The elemental S could react with oleylamine to produce highly reactive small molecule H2S, which then precipitate with Cu, Zn and Sn species to form kesterite CZTS nanoparticles. As for the case of DDT, the covalent bonded S is very stable and difficult to be broken down to release S, leading to formation of wurtzite phase. TAA exhibit reaction rate between elemental S and DDT, therefore yields a mixture of kesterite and wurtzite pahses. The optical and electrical properties of kesterite and wurtzite were evaluated and showed similar properties. The optical band gaps of kesterite phase and wurtzite phase were estimated based on absorption measurements to be 1.48 eV and 1.55 eV respectively. The valance band and conduction band energy levels are determined using CV measurements to be -5.37 and -3.85 eV (kesterite), -5.60 and -3.91 eV (wurtzite). Compared with CZTS nanoparticles ink approach, a greener synthesis route based on CuS, ZnS and SnS2 nanoparticles with water or ethanol solvent was developed. The post-annealing plays an important role in the phase evolution from binary phases into quaternary CZTS phase. It was found that pure CZTS phase formed at 300°C, 400°C and 450°C. The selenization process was performed on the nanoparticles precursor film. CZTSSe thin film solar cells were fabricated following Mo/CZTSSe/CdS/ZnO/ITO/Au architecture. The as-fabricated device exhibited a total area efficiency of 5.12% with Voc of 378 mV, Jsc of 26.2 mA/cm2 and FF of 51.7%. These results are comparable with some of the best performing nanoparticles based CZTSSe solar cells. Combined with the low-cost, environmentally friendly and upscalable fabrication steps, our synthesis method is highly promising for potential industry scale application.